2012
DOI: 10.1116/1.4731196
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring of molybdenum and tungsten surfaces by low-energy helium ions

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers)Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 22 publications
8
103
1
1
Order By: Relevance
“…This layer depth is in-line with the calculations from the Baldwin formula and proof that a significant layer of W fuzz can grow over a short timescale. It must be mentioned that the Baldwin formula is based on data only at surface temperatures of 1120 K and 1320 K. Some work has shown this formula to overestimate growth rates for T surf > 1400 K [3,12]. It has been suggested that a factor dependent on He ion energy might be missing from the formula [12] and that re-crystallization effects might be competing with the surface changes at higher temperatures [3].…”
Section: Comparison Of Alcator C-mod Results To Pisces and Pilot-psimentioning
confidence: 99%
See 4 more Smart Citations
“…This layer depth is in-line with the calculations from the Baldwin formula and proof that a significant layer of W fuzz can grow over a short timescale. It must be mentioned that the Baldwin formula is based on data only at surface temperatures of 1120 K and 1320 K. Some work has shown this formula to overestimate growth rates for T surf > 1400 K [3,12]. It has been suggested that a factor dependent on He ion energy might be missing from the formula [12] and that re-crystallization effects might be competing with the surface changes at higher temperatures [3].…”
Section: Comparison Of Alcator C-mod Results To Pisces and Pilot-psimentioning
confidence: 99%
“…It must be mentioned that the Baldwin formula is based on data only at surface temperatures of 1120 K and 1320 K. Some work has shown this formula to overestimate growth rates for T surf > 1400 K [3,12]. It has been suggested that a factor dependent on He ion energy might be missing from the formula [12] and that re-crystallization effects might be competing with the surface changes at higher temperatures [3]. Despite concerns about the formula raised in the literature, the comparison with the Alcator C-Mod results, which were also performed at T surf > 1400 K, and the Baldwin formula resulted in good agreement.…”
Section: Comparison Of Alcator C-mod Results To Pisces and Pilot-psimentioning
confidence: 99%
See 3 more Smart Citations